Managing digital cultural objects : analysis, discovery and retrieval - Foster, Allen, 1968-; Rafferty, Pauline, 1959- (Chicago : Neal-Schuman, an imprint of the American Library Association, 2016)
'This book explores the analysis and interpretation, discovery and retrieval of a variety of non-textual objects, including image, music and moving image... The book covers a broad range of topics and draws from a number of disciplines, including information retrieval, library and information science, digital preservation and digital humanities, and even cultural theory, digital media studies and art history'--
Part 1. Analysis and Retrieval of Digital Cultural Objects. 1. Managing, searching and finding digital cultural objects : putting it in context / Pauline Rafferty -- 2. Data modelling for analysis, discovery and retrieval / Sarah Higgins -- 3. The digital traces of user-generated content : how social media data may become the historical sources of the future / Katrin Weller -- Part 2. Digitization Projects in Libraries, Archives and Museums: Case Studies. 4. Visual digital humanities : using image data to derive approximate metadata / H.M. Dee, L.M. Hughes, G.L. Roderick and A.D. Brown -- 5. Managing and preserving digital collections at the British Library / Maureen Pennock and Michael Day -- 6. Digital preservation of audio content / Will Prentice -- Part 3. Social Networking and Digital Cultural Objects. 7. Photos : Flickr, Facebook and other social networking sites / Corinne Jgensen -- 8. Searching and classifying affinities in a web music collection / Nicola Orio -- 9. Film retrieval on the web : sharing, naming, access and discovery / Kathryn La Barre and Rosa In{u3973} de Novais Cordeiro.
'First published in the United Kingdom by Facet Publishing, 2016.'--Title page verso.
Includes bibliographical references and index.
Keywords: Metadata; Electronic information resources -- Management; Information retrieval; Digital media; Digital preservation; Digital humanities; Cultural property -- Digitization